2010
DOI: 10.1161/circimaging.109.908152
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Implications of Left Ventricular Filling Pressure With Exercise

Abstract: Background-The estimation of left ventricular (LV) filling pressure from the ratio of transmitral and annular velocities (E/eЈ) after exercise echocardiography may identify diastolic dysfunction in patients who complain of exertional dyspnea. This study sought to determine the relative contributions of exercise E/eЈ and ischemia to outcomes in patients referred for exercise echocardiography. Methods and Results-Rest and exercise E/eЈ were obtained in 522 patients referred for exercise echocardiography, who wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(68 citation statements)
references
References 39 publications
(46 reference statements)
4
60
0
4
Order By: Relevance
“…Importantly, the elevated E/e′ ratio with exercise has been associated with adverse cardiovascular outcomes even when detectable ischemia is considered [37]. Diastolic stress testing with intravenous dobutamine infusion, although infrequent in current clinical practice, has also been shown to predict clinical events in cardiac patients [38].…”
Section: Diastolic Stress Testmentioning
confidence: 99%
“…Importantly, the elevated E/e′ ratio with exercise has been associated with adverse cardiovascular outcomes even when detectable ischemia is considered [37]. Diastolic stress testing with intravenous dobutamine infusion, although infrequent in current clinical practice, has also been shown to predict clinical events in cardiac patients [38].…”
Section: Diastolic Stress Testmentioning
confidence: 99%
“…22 Furthermore, a recent study showed the incremental prognostic value of exercise E/eЈ ratio over clinical variables and exercise wall motion score index. 23 Collectively, there is growing evidence that the diastolic stress test can provide important diagnostic findings that can be helpful in the management of patients presenting with dyspnea of an unclear etiology. Because dobutamine is a vasodilator as well as an inotrope, the hemodynamic response to dobutamine is very different from that of exercise.…”
Section: Diastolic Stress Testmentioning
confidence: 99%
“…An increase in the E/e´ ratio under physical exercise indicates a concomitant increase in LV end-diastolic pressures and a worse prognosis. 15,16 Strain rate during the isovolumetric relaxation time (IVRsr) or early diastolic strain rate (e´sr), derived from global longitudinal speckletracking strain, were recently proposed to estimate LV filling pressures, although both parameters are still experimental. 17 …”
Section: Diastolic Functionmentioning
confidence: 99%